2016
DOI: 10.1007/s10792-016-0318-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and ophthalmoscopic evaluation of apocynin on experimental proliferative vitreoretinopathy in rabbit eyes

Abstract: The aim of the current study was to evaluate the effect of apocynin (APO) on the development of proliferative vitreoretinopathy (PVR). New Zealand-type male rabbits were randomly grouped into three as follows: (1) Sham group rabbits which were applied intraperitoneal (i.p.) vehicle without PVR; (2) PVR group rabbits where PVR was created and an i.p. vehicle was administered for 21 successive days; (3) PVR + APO group rabbits where PVR was created and i.p. APO was administered for 21 successive days. Fundus exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…While the rabbit is a commonly utilized animal model for PVR due to the large size of the globe and its ability to manifest features similar to the human condition, existing models have not consistently demonstrated both epi-and subretinal membranes, the key histologic features of human PVR. 16,29,[39][40][41][42][43][44][45][46] In addition, our data demonstrate the involvement of multiple collagen species in the development of PVR membranes, suggesting that multiple profibrotic signaling pathways may be involved. These rabbit data also validate the presence of additional features of human PVR, i.e., increased microglial invasion into epiretinal membranes, Mϋller glia activation, and RPE de-differentiation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While the rabbit is a commonly utilized animal model for PVR due to the large size of the globe and its ability to manifest features similar to the human condition, existing models have not consistently demonstrated both epi-and subretinal membranes, the key histologic features of human PVR. 16,29,[39][40][41][42][43][44][45][46] In addition, our data demonstrate the involvement of multiple collagen species in the development of PVR membranes, suggesting that multiple profibrotic signaling pathways may be involved. These rabbit data also validate the presence of additional features of human PVR, i.e., increased microglial invasion into epiretinal membranes, Mϋller glia activation, and RPE de-differentiation.…”
Section: Discussionmentioning
confidence: 53%
“…29 Elevated αSMA expression in epiretinal membranes at time points ranging from 22 days to 11 weeks post-induction have been reported, but subretinal data are unavailable. 29,[42][43][44][45][46] Khanum et al reported evaluation of their rabbit model one and 30 days postinduction; however, it is unclear from their figures from which time points their photomicrographs of H&E-stained or immunolabeled sections were obtained. 40 Our 6hour and 2-day data broadly align with the findings of Zahn et al at days 3 and 7 postinduction, in which they assayed Mϋller glia, microglia, and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…After an anatomical observation, globes were embedded in paraffin, sectioned (5-μm-thick) into retinal slices, and stained with hematoxylin-eosin (H&E) for histological examination using a light microscope (Carl Zeiss, Oberkochen, Germany). PVR severity was graded as described by Ozer et al [32] . Immunofluorescence Cryosections were blocked with 5% bovine serum albumin containing 0.3% Triton-X100 at room temperature for 1h and then incubated with primary antibodies against alpha-smooth muscle actin (αSMA, 1:200, MA5-11547, Thermo Scientific, Waltham, MA, USA) and GFAP conjugated with Alexa Fluor 488 (1:50, 53-9892-82, Thermo Scientific) overnight at 4°C, followed by corresponding secondary antibodies for 2h at room temperature.…”
Section: Platelet-rich Plasma Preparation and Traumatic Pvr Model Ind...mentioning
confidence: 99%
“…Twelve adult pigmented rabbits were selected, each weighing about 2-2.5kg, After extracted 0.2ml vitreous,12 traumatic PVR model rabbits were prepared by intravitreal injection of 0.1ml platelet rich plasma and 0.1mlPBS [14,15]. They were randomly divided into blank group, control group (0.1mlprp + 0.1mlpbs) and experimental group: (0.1mlPRP + 0.1ml 20ug/ml artesunate).…”
Section: Animal Experimentsmentioning
confidence: 99%